A numerical model for optimal receiver array and mass flow rate in residential solar water heating systems - Rigardt Alfred Maarten Coetzee; Aggrey Mwesigye; Zhongjie Huan (International Journal of Sustainable Energy, 2018)
In this paper, the performance of a pressurised evacuated tube solar collector system using internal heat pipes is presented. The system was optimised for the seasonal supply of hot service water for residential use in Pretoria, South Africa. The prediction of seasonal hourly performance trends along with the maximum thermal performance at the optimal receiver array and manifold mass flow rate was of major concern in this investigation. A mathematical model representing the thermal performance of the system was developed and numerically implemented in Engineering Equation Solver. The dynamic performance of collectors with 15, 20 and 25 tubes was determined throughout all the seasons. Moreover, the performance of the residential solar water heating system with a 20-tube collector was investigated in detail for mass flow rates of 0.03, 0.05 and 0.07 kg/s.